Assessment of effect modification of statins on new-onset diabetes based on various medical backgrounds: a retrospective cohort study - Keiko Yamazaki; Yasuo Takahashi; Kotoe Teduka; Tomohiro Nakayama; Yayoi Nishida; Satoshi Asai (BMC, 2019)
Abstract Background The aim of this study was to investigate the association between statin use and new-onset diabetes in clinical settings and to assess its effect modification (heterogeneity) among patients with various medical histories and current medications. Methods In a total of 12,177 Japanese patients without diabetes, from December 2004 to November 2012, we identified 500 statin users and 500 matched non-users using propensity-score matching. Patients were followed until December 2017. We estimated the hazard ratios of new-onset diabetes associated with statin use. We also tested the heterogeneity of the treatment effect by evaluating subgroup interactions in subgroups according to sex, age, medical history, and current medication. Results New-onset diabetes had occurred in 71 patients (13.6%) with statin use and 43 patients (8.3%) with non-use at 5 years (hazard ratio, 1.66; 95% confidence interval [CI], 1.11 to 2.48; P = 0.0143), and in 78 patients (15.6%) with statin use and 48 patients (9.6%) with non-use at 10 years (hazard ratio, 1.61; 95% CI, 1.10 to 2.37; P = 0.0141). There were no significant treatment-by-subgroup interactions in all subgroups defined according to sex, age, medical history, and current medication. Conclusions In patients with various clinical backgrounds, those who received statin therapy had a higher risk of new-onset diabetes at 5 and 10 years than those who did not receive it. Effect modification of statins on new-onset diabetes was not found in patient populations defined according to various comorbid diseases or concomitant drugs.